A glass matrices-assisted quantum dots-based biosensor for selective capturing and detection of Escherichia coli. (21st November 2022) - Pant, Anjali; Kaur, Taranvir; Sharma, Teenu; Singh, Joga; Suttee, Ashish; Barnwal, Ravi Pratap; Kaur, Indu Pal; Singh, Gurpal; Singh, Bhupinder
Abstract: Bacterial contamination of water and food is a grave health concern rendering humans quite vulnerable to disease(s), and proving, at times, fatal too. Exploration of the novel diagnostic tools is, accordingly, highly called for to ensure rapid detection of the pathogenic bacteria, particularly Escherichia coli . The current manuscript, accordingly, reports the use of silane-functionalized glass matrices and antibody-conjugated cadmium telluride (CdTe) quantum dots (QDs) for efficient detection of E. coli . Synthesis of QDs (size: 5.4–6.8 nm) using mercaptopropionic acid (MPA) stabilizer yielded stable photoluminescence (∼62%), corroborating superior fluorescent characteristics. A test sample, when added to antibody-conjugated matrices, followed by antibody-conjugated CdTe-MPA QDs, formed a pathogen-antibody QDs complex. The latter, during confocal microscopy, demonstrated rapid detection of the selectively captured pathogenic bacteria (10 microorganism cells/10 μL) with enhanced sensitivity and specificity. The work, overall, encompasses establishment and design of an innovative detection platform in microbial diagnostics for rapid capturing of pathogens in water and food samples. HIGHLIGHTS: Antibody-mediated fluorescent biosensor for efficient capturing and detection of E. coli . Bioconjugation of QDs and E. coli antibodies. Qualitative, quantitative and selective assessment of E. coli in contaminated water using CLSM. High sensitivity of glass matrix biosensor, with detection limit of 10 microorganisms/10 mL. Capability of technology extension for detecting other microbial pathogens. Graphical Abstract